KAFIRNYA FILSUF MUSLIM: Ibn Rusyd Meluruskan al-Ghazali - Muhammad Mahfud Ridwan (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
Ibn Rusyd is seen figure renewal and generating Aristotle philosophy that has long been buried or torpor. Among his famous works is about criticism of al-Ghazali thought about keqadiman nature, knowledge of God and theresurrection of man. Ibn Rusyd argued about the views of the philosophersof the latter. Al-Ghazali accusations against the philosophers is not truebut just different points of view are made as if the philosophers have deviated from monotheism even considered infidels.Keywords: Ibn Rusyd, al-Ghazali, critics